2019
DOI: 10.3390/polym11122112
|View full text |Cite
|
Sign up to set email alerts
|

Hydrofilm Polyurethane Films Reduce Radiation Dermatitis Severity in Hypofractionated Whole-Breast Irradiation: An Objective, Intra-Patient Randomized Dual-Center Assessment

Abstract: Radiation-induced skin injury represents the most frequent side effect in breast cancer patients undergoing whole-breast irradiation (WBI). Numerous clinical studies on systemic and topical treatments for radiation dermatitis have failed to provide sustainable treatment strategies. While protective skin products such as dressings are undoubtedly the standard of care in wound care management, their utilization as preventive treatment in radiotherapy has been somewhat neglected in recent years. In this prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 36 publications
3
22
0
5
Order By: Relevance
“…Along with objectivity, a continuous scale enumerating even slight changes in the skin color also allows us to draw precise conclusions on both the development of RID and the efficacy of specific treatments [ 2 , 5 , 11 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with objectivity, a continuous scale enumerating even slight changes in the skin color also allows us to draw precise conclusions on both the development of RID and the efficacy of specific treatments [ 2 , 5 , 11 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In light of the aforementioned and varying study results, this quintessence was not entirely unexpected. Many authors, therefore, concluded that future studies should endeavor to meet the requirement for a more objective approach in the RID evaluation process [ 5 , 6 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation dermatitis severity was reduced in patients with breast cancer radiotherapy after prophylactic use of Hydrofilm (Paul Hartmann AG, Heidenheim, Germany) compared with control (Schmeel et al, 2019). A study examined the effect of a film dressing (Airwall) in the management of acute radiation dermatitis induced by proton beam therapy.…”
Section: Radiation Dermatitismentioning
confidence: 99%
“…Considerando as mulheres diagnosticadas com câncer de mama, o tratamento radioterápico tem sido amplamente difundido, reduzindo as taxas de recorrência local após procedimentos cirúrgicos e/ou quimioterapia. Entretanto, a preocupação com as reações cutâneas adversas, associadas à radioterapia, tem sido constante, embora sejam bem toleradas pela maioria das pacientes 7,8 .…”
Section: Introductionunclassified